Public confidence towards judiciary court: An empirical study in Bangladesh - Jalal, Md Sha; Hasan, Md Akramul; Akter, Mahmuda (International Journal of Emerging Trends in Social Sciences, 2024)
The judiciary is the most significant component of the criminal justice system, which ensures the legal rights of citizens and is strongly linked to public confidence. The judiciary system of Bangladesh is ineffective and inadequate in safeguarding citizens' rights, highlighting the need for the building of trust between citizens and the judiciary system. The main objective of this study was to explore the nature of public trust in the judiciary system in Bangladesh. Moreover, it also identified the entire public perception of the judicial system, which influences public trust in the judiciary. The study was quantitative in nature which followed the survey method, and the data was collected from 52 respondents. This study found that around 63.5% of the participants expressed a negative perception regarding the court's integrity and meticulousness in dealing with people. At the same time, specifically 38.5% who agreed and 48.1% who strongly agreed, believe that corruption has a substantial impact on the level of public confidence in the judiciary court system. Additionally, 51.9% of the respondents believed that unfriendly behavior has an impact on the level of public confidence in the judiciary court system. Most importantly, the majority of respondents (76.9%) assess the courts' performance in ensuring responsibility as either low (53.8%) or average (23.1%). Finally, this study suggests that the government and concerned authorities should take proactive measures to enhance public confidence in the justice system.